PENGARUH PENERAPAN MODEL PEMBELAJARAN AKTIF TIPE LEARNING TOURNAMENT TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMP NEGERI 10 PADANG - Sartika, Titi; Harisman, Yulyanti; sovia, Anny (STKIP PGRI Sumbar, 2014)
Â Background of this research is studentâs understanding of mathematic conseptual which still low and also students less motivation in learning mathematic. The purpose of this research is to know whether studentâs mathematic conseptual understanding by active learning is better than using convensional learning at VIII grade students in Junior High School Number 10 Padang and how is studentâs motivation in learning mathematic by using Tournament active Learning. This research is experimental research by using random sampling design. The instrument that is used in this research is test and questionnaire motivation of studentâs mathematic conseptual understanding. The technique analysis for hypothesis is t test by using soft are MINITAB. Based on the data analysis, the research found P-value is less than Î± value in here H0 rejected, so hypothesis of this research is accepted, meanwhile the result of percentage data analysis for each item and indicator totallây is good. From the analysis above, it can be conluded that studentâs motivation and studentâs mathematic conseptual understanding by using Tournament Active Learning is better than using conventional learning at VIII grade student in Junior High School Number 10 Padang and also, studentâs motivation in learning mathematic at VIII grade students of Junior High School Number 10 Padang by using Tournament Active Learning is high.